PSYCHOLOGICAL AND PROFESSIONAL PROBLEM OF ACADEMIC PERFORMANCE OF THE STAFF OF HIGHER EDUCATIONAL INSTITUTIONS - Nazokat Norova (Web of Journals Publishing, 2024)
This article is devoted to the problem of professional burnout among teachers of higher education. This problem is widespread in higher education institutions around the world. In recent years, due to the constant increase in the workload of the teaching staff, it has become especially relevant for our country. In this paper, the empirical data accumulated to date on the professional burnout of university teachers from different regions of the Republic of Uzbekistan were analyzed. The stages of development of professional burnout and the accompanying symptoms were traced, the causes of this phenomenon were analyzed in detail and risk groups were identified. The analysis showed that the maximum risk of developing professional burnout is typical for middle-aged teachers with significant teaching experience, while women develop symptoms of professional burnout more often than men. The data obtained confirm the importance of this problem for most teachers in the Russian Federation and emphasize the need for preventive measures to prevent the development of such conditions, especially in risk groups.
Keywords: professional burnout; emotional burnout; preventive measures; higher education institutions; causes of professional burnout; faculty; empirical data.